2016
DOI: 10.1016/j.hpb.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparing early and delayed repair of common bile duct injury to identify clinical drivers of outcome and morbidity

Abstract: Background: Outcomes following repair of common bile duct injury (CBDI) are influenced by center and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 33 publications
3
42
0
3
Order By: Relevance
“…Performing the definitive operation immediately (during the 1st 72 h), in the intermediate period (between 72 h and 1.5 months) or in the late period (after1.5 months) from injury, did not have any significant effect on our late biliary morbidity. Similarly, it did not influence postoperative morbidity in Pottakkat et al, 2010 [ 3 ], Patrono et al, 2015 [ 4 ], Bansal et al, 2015 [ 36 ], Huang et al, 2014 [ 38 ], Kirks et al, 2016 [ 83 ], and Perera et al, 2011 [ 84 ], studies. However, most authors advice late repair of LC-BDIs (≤6 weeks) from LC [ 29 , 53 , 85 ]; this allows the abdominal inflammation to subside prior to definitive repair leading to its success [ 50 , 86 ].…”
Section: Discussionmentioning
confidence: 93%
“…Performing the definitive operation immediately (during the 1st 72 h), in the intermediate period (between 72 h and 1.5 months) or in the late period (after1.5 months) from injury, did not have any significant effect on our late biliary morbidity. Similarly, it did not influence postoperative morbidity in Pottakkat et al, 2010 [ 3 ], Patrono et al, 2015 [ 4 ], Bansal et al, 2015 [ 36 ], Huang et al, 2014 [ 38 ], Kirks et al, 2016 [ 83 ], and Perera et al, 2011 [ 84 ], studies. However, most authors advice late repair of LC-BDIs (≤6 weeks) from LC [ 29 , 53 , 85 ]; this allows the abdominal inflammation to subside prior to definitive repair leading to its success [ 50 , 86 ].…”
Section: Discussionmentioning
confidence: 93%
“…Clinical manifestations of bile leak include persistent abdominal tenderness, generalized malaise and anorexia. Bile leak after surgery resulting in intraperitoneal bile collection is typically not contaminated by bacterium and usually does not result in severe bile peritonitis Detecting and locating bile leak may not be easy; patients usually undergo US and CT examinations but these methods can not reliably distinguish bile leak from other postoperative fluid collection such as blood, pus, or serous fluid because of similar densities [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Different opinions exist related to the best moment to carry on the repair, Strasber [9] has suggested to wait 3 months in lesions with confluence lost meanwhile ischemia is delimit, as lesion is always higher than originally appreciated. In the same way, Santibañez [15] considered that repairing should wait 6 to 8 weeks in order to allow inflammation to be limited; on the contrary, recent reports like the ones from Stilling [16] or Kirk [17] concluded that the repair moment of a bilioenteric derivation by itself, did not modify the long term result. Stewart and Way [18] in a multivariate analysis on 307 patients, revealed that a derivation success depends on complete eradication of the abdominal infection, identification of the lesion level through a cholangiography, adequate surgical technique and an experienced biliary team; when these objectives are achieved, repair could be performed at any time with the expectation of a favorable result without any reason to delay the procedure for an arbitrary time [18].…”
Section: Figura 2 Irrigation Of the Bile Duct / C H A: Common Hepamentioning
confidence: 99%